Draft Annual Plan 1980-81 (In 4 Volumes) Vol. IV Haryana State - Planning Commission (Planning Commission, 1979)
One Outlay for the Five Year Plan 1978-83 under the development head, General Education fl has been fixed at Rs. 4860. 00 lakhs. During the year 1978-79, the first year of take Plan, an expenditure of Rs. 81 R 74 lakhs has been incurred and for the year 1979-80, the Plan outlay has been fixed at Rs. 743.00 .lakhs. An outlay of Rs, 80000 lakhs 'has been proposed for the year 1980-81. The sub-head-wise break-up of Five Year Plan 1978- 83, actual expenditure for 1978-79, outlay for 1979-80,. anticipated expenditure 1979-80 and proposed outlay for 1980-81.
Government of Haryana
Planning Department Government of Haryana
Keywords: General Education; Art and Culture; Industrial Training; Ayurveda; Health and medical Education; Water Supply and Sewerage; Housing; Urban Development; Information and Publicity; Labour and Labour Welfare; Secretariat Economic Services; Economic Advice and Statistics; Printing and stationery; General Administration